On Upper and Lower 𝛽(𝜇𝑋,𝜇𝑌)-Continuous Multifunctions - Chawalit Boonpok (International Journal of Mathematics and Mathematical Sciences)
A new class of multifunctions, called upper (lower) 𝛽(𝜇𝑋,𝜇𝑌)-continuous multifunctions, has been defined and studied. Some characterizations and several properties concerning upper (lower) 𝛽(𝜇𝑋,𝜇𝑌)-continuous multifunctions are obtained. The relationships between upper (lower) 𝛽(𝜇𝑋,𝜇𝑌)-continuous multifunctions and some known concepts are also discussed.